Subjektivität und Kunst: Konstitution der Moderne nach Hegel und Nietzsche - Jung, Daehun (transcript, 2017)
Modernity is shaped by a particular configuration between subjectivity and art. But how exactly can this be grasped? This volume pursues this question with the use of a deconstructive interpretation of the texts of Hegel and Nietzsche.